Seroprevalence of hepatitis E virus (Hepeviridae: Orthohepevirus: Orthohepevirus A) among pregnant women in the highly endemic region of Kyrgyzstan - G. I. Alatortseva; Z. Bakirova; L. N. Lukhverchik; A. Z. Nurmatov; Z. S. Nurmatov; K. E. Tashov; L. N. Nesterenko; Е. Yu. Malinnikova; O. T. Kasymov; M. I. Mikhailov; V. V. Zverev (Вопросы вирусологии, 2020)
Introduction. Hepatitis E (HE) is an important public health problem worldwide and is especially significant for pregnant women, among whom the associated mortality rate reaches 25%. The distribution of HE serological markers in this cohort in the endemic regions of Central Asia is poorly understood. The aim of the study was to assess the seroprevalence of HEV among pregnant women in the region of Kyrgyzstan where an increased incidence of HE is reported. Material and methods. Blood serum of pregnant women, obtained from medical institutions in Bishkek, city of Osh and Osh region in the period from September 2016 to October 2019, and the control group of clinically healthy women were tested using the test systems “DS-IFA-ANTI-HEV-G” and “DS-IFA-ANTI-HEV-M” (NPO “Diagnostic Systems”, Russia). Results. IgG antibodies to HEV were detected in 87 (5.9%) of 1472 examined pregnant women, IgM antibodies -in 64 (4.8%) of 1378, while 5 (0.34%) samples were simultaneously positive for IgG and IgM antibodies. The rates of detection of antibodies to HEV in women of three age categories from 17 to 36 years old in the studied and control groups were similar. The analysis of the seasonal dynamics of HEV seroprevalence in pregnant women in the period from February to September 2019 showed a tendency towards an increase in the values of the positivity coefficient of specific IgM antibodies by the beginning of the autumn. Antibodies to HEV were detected with highest frequency in women from Osh region. Conclusions. A high risk of HEV infection for pregnant women in the surveyed region had been shown.